PRОSОDIK VА EKSTRАLINGVISTIK VОSITАLАRNING MULОQОTDАGI O‘RNI - Mаhliyo Dаrvishаliyеvа, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The article analyzes the emergence of speech prosodic and extralinguistic means in the process of communication using examples.